Fungal nomenclature evolving: changes adopted by the 19(th) International Botanical Congress in Shenzhen 2017, and procedures for the Fungal Nomenclature Session at the 11(th) International Mycological Congress in Puerto Rico 2018 - Hawksworth, David L. (IMA Fungus, 2017)
This article summarizes the key changes in the rules relating to the nomenclature of fungi made at the XIX International Botanical Congress in Shenzhen, China, in July 2017. Most significant was the decision to transfer decision-making on matters related only to the naming of fungi from International Botanical to International Mycological Congresses (IMCs). The rules relating to fungi are to be grouped together in a separate section of the International Code of Nomenclature for algae, fungi, and plants (ICN). The way in which the Fungal Nomenclature Session will operate at the upcoming IMC in Puerto Rico in 2018 is summarized and the timetable for new proposals is presented. In addition, approval for names included on lists of protected names to be protected against unlisted as well as known competing names were passed, as were some simplifications relating to the naming of pleomorphic fungi. From 1 January 2019, it will also be necessary to deposit details of lecto-, neo-, and epitypifications in one of the recognized repositories of fungal names in order for them to be validly published and to establish their priority. Various aspects relating to typifications were referred to a new Special Committee, with a separate Special Subcommittee charged with addressing the issue of using DNA sequences as types for all groups covered by the ICN. It is anticipated that the Shenzhen Code will be published in the first half of 2018.